The effects of total quality management practices to employees' job satisfaction / Azwan Shah Aminuddin ... [et al.] - Aminuddin, Azwan Shah; Zakaria, Ibhrahim; Mat Halif, Mazuin; Mansor, Farah Ahlami; Setapa, Mariam (Faculty of Business and Management, 2022)
The effects of Total Quality Management (TQM) on employees' job satisfaction has been studied extensively in worldwide. Moreover, there are not many studies about the effects of TQM and job satisfaction. The purpose of this research is to study the effect of TQM on job satisfaction. Five hypotheses were developed in this paper. This study is useful to the top management in the public sector as a guide to improve their current employees' capabilities and organization performance. It is also can improve the quality of work, indirectly improve the productivity of employees at their organization. This study was a cross-sectional study. A stratified sampling technique was used in collecting data from 261 employees in Majlis Bandaraya Melaka Bersejarah (MBMB). The results of the study supported only three from five hypotheses. Accordingly, top management commitment and reward and recognition are the most influential factors of TQM practices towards employee' job satisfaction.